A randomised controlled trial of single phototherapy with reflecting curtains and double phototherapy in term newborns with hyperbilirubinemia - Intan Juliana, Abd Hamid (2011)
To compare the efficacy of single phototherapy with reflecting curtains and double phototherapy in treating neonatal jaundice. Randomized controlled clinical trial. NICU Hospital Universiti Sains Malaysia, Kelantan, Malaysia. Term newborns with severe neonatal jaundice in the first 2 weeks of life. Single phototherapy with reflecting curtains (intervention group, n=63) was compared with double phototherapy (control group, n=54). The primary outcome was the mean difference in total serum bilirubin measured at baseline and after 4 hours of phototherapy. The secondary outcome was the duration of phototherapy. The mean (standard deviation) decrease in serum bilirubin after 4 hours of phototherapy in the intervention group was 24.16 (27 .87) ~mol/L and the control group was 21.11 (24.69) ~mol/L (p 0.536), statistically not significant. Cox proportional hazards regression analysis indicated that there was no statistically significant difference in duration of phototherapy in both intervention (SPRC) and control (DP) (.1 change 1.641; p 0.200; hazard ratio 0.784; 95% confidence interval 0.542 to 1.136). There were no other significant adverse events noted. This study suggested that single phototherapy with reflecting curtains are equally effective as double phototherapy in treating severe neonatal hyperbilirubinaemia.